Advanced Automation Solutions For Steelmaking And Environmental Plants - Andreas Rohrhofer (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2017)
Reliable high end automation and process optimization systems are main factors for excellent product quality, safe operation and maximized plant performance in the steel industry and its designated environmental plants. Primetals Technologies introduces new automation packages for consequent safe and cost efficient production. Many areas within the steelplant interested to be monitored and measured automatically are not implemented in the automation system due to limited access or technical reasons. A wireless, self-organizing network facilitates wide ranging data transmission in previously inaccessible areas and opens up a wide range of new opportunities. With Fluid Guard a system to detect leakages with highest accuracy and reacts properly for all kind of water cooled circuits is available, improving the safety in steelmaking process. Lance Guard can be utilized for all fully automatic and semi-automatic lance appliances, but is especially suitable for the products of Primetals Sublance Standard/2.0 and LiquiRob applications, since these systems make seamless integration particularly simple. Manual lance appliances may also be tested and diagnosed. Environmental plants have become a main part in steelmaking plants. Highest performance in combination with optimized energy consumption is the main target in Primetals Technologies’ innovations in automation optimization packages for dedusting systems. A new approach for preventive maintenance and operator assistance is introduced with the Acoustic Expert System. In combination with the new Ask cloud based system, Primetals enables a 24/7 monitoring and a whole lifetime observation of any equipment within a steelplant. Furthermore it is now enabled to check the condition of the plant at a fingertip at any time.